Degradation of tetrabromobisphenol A (TBBA) with calcium hydroxide: a thermo-kinetic analysis. Issue 10 (28th February 2023) - Ali, Labeeb; Sivaramakrishnan, Kaushik; Kuttiyathil, Mohamed Shafi; Chandrasekaran, Vignesh; Ahmed, Oday H.; Al-Harahsheh, Mohammad; Altarawneh, Mohammednoor
Abstract : Thermal treatment of bromine-contaminated polymers ( i.e., as in e-waste) with metal oxides is currently deployed as a mainstream strategy in recycling and resources recovery from these objects. Abstract : Thermal treatment of bromine-contaminated polymers ( i.e., as in e-waste) with metal oxides is currently deployed as a mainstream strategy in recycling and resources recovery from these objects. The underlying aim is to capture the bromine content and to produce pure bromine-free hydrocarbons. Bromine originates from the added brominated flame retardants (BFRs) to the polymeric fractions in printed circuits boards, where tetrabromobisphenol A (TBBA) is the most utilized BFR. Among notable deployed metal oxides is calcium hydroxide, i.e., Ca(OH)2 that often displays high debromination capacity. Comprehending thermo-kinetic parameters that account for the BFRs:Ca(OH)2 interaction is instrumental to optimize the operation at an industrial scale. Herein, we report comprehensive kinetics and thermodynamics studies into the pyrolytic and oxidative decomposition of a TBBA:Ca(OH)2 mixture at four different heating rates, 5, 10, 15, and 20 °C min −1, carried out using a thermogravimetric analyser. Fourier Transform Infrared Spectroscopy (FTIR) and a carbon, hydrogen, nitrogen, and sulphur (CHNS) elemental analyser established the vibrations of the molecules and carbon content of the sample. From the thermogravimetric analyser (TGA) data, the kinetic and thermodynamic parameters were evaluated using iso-conversional methods (KAS, FWO, and Starink), which were further validated by the Coats–Redfern method. The computed activation energies for the pyrolytic decomposition of pure TBBA and its mixture with Ca(OH)2 reside in the narrow ranges of 111.7–112.1 kJ mol −1 and 62.8–63.4 kJ mol −1, respectively (considering the various models). Obtained negative Δ S values suggest the formation of stable products. The synergic effects of the blend exhibited positive values in the low-temperature ranges (200–300 °C) due to the emission of HBr from TBBA and the solid–liquid bromination process occurring between TBBA and Ca(OH)2 . From a practical point of view, data provided herein are useful in efforts that aim to fine-tune operational conditions encountered in real recycling scenarios, i.e., in co-pyrolysis of e-waste with Ca(OH)2 in rotary kilns.